Prevalence and antibiotic susceptibility of escherichia coli in processed food at retail level / Suzanne Anak Kudang - Kudang, Suzanne (2017)
Escherichia coli is a Gram negative rod in family Enterobacteriaceae and most of Escherichia coli is harmless. In spite of that, human can be infected with pathogenic Escherichia coli strains through consumption of contaminated water and food with faeces or from cross-contamination with another food source. The aim of this study is to isolate and detect Escherichia coli from processed food at retail level and to determine the occurrence of antibiotic resistance of Escherichia coli by using disc diffusion method. In this study, it showed positive result of Escherichia coli from the three out of four samples obtained from supermarket and wet market. Furthermore, the multiple antibiotic resistance (MAR) index for antibiotic susceptibility result showed all positive Escherichia coli samples have high score which is greater than 0.2 to indicate that the pathogens were originated from the higher risk sources where antibiotics are often used. Bigger study on a bigger scale are recommended for a better understanding on the prevalence and antibiotic susceptibility of Escherichia coli in processed food at retail level.